Cybersecurity as it relates to perfusion. - Lung, Kara (Journal of Extra-Corporeal Technology, 2026)
Perfusionists must maintain strong digital security habits, know the inherent risks of devices in use, and have a healthy respect for the consequences of a security breach at a hospital. While perfusion has largely been able to operate without much interaction with cybersecurity experts, the relentless advancement of the digital age means that perfusionists cannot remain oblivious to the intersection of their devices and hospital digital security. This article provides a historical overview of healthcare cybersecurity with specific recommendations for perfusion teams looking to ensure best practices for protected health information (PHI). Critical recommendations include keeping physical copies of downtime procedures, routine practice of downtime procedures, discussion with the hospital information technology (IT) team to confirm perfusion-based asset lists, and the creation of an American Society of Extracorporeal Technology (AmSECT) standard or guideline regarding attention to cybersecurity.